Clinical features of Candidiasis in patients with inherited interleukin 12 receptor β1 deficiency (2014)
ABSTRACT: Background: Interleukin 12Rβ1 (IL-12Rβ1)-deficient patients are prone to clinical disease caused by mycobacteria, Salmonella, and other intramacrophagic pathogens, probably because of impaired interleukin 12-dependent interferon γ production. About 25% of patients also display mucocutaneous candidiasis, probably owing to impaired interleukin 23-dependent interleukin 17 immunity. The clinical features and outcome of candidiasis in these patients have not been described before, to our knowledge. We report here the clinical signs of candidiasis in 35 patients with IL-12Rβ1 deficiency. Results: Most (n = 71) of the 76 episodes of candidiasis were mucocutaneous. Isolated oropharyngeal candidiasis (OPC) was the most common presentation (59 episodes, 34 patients) and was recurrent or persistent in 26 patients. Esophageal candidiasis (n = 7) was associated with proven OPC in 2 episodes, and cutaneous candidiasis (n = 2) with OPC in 1 patient, whereas isolated vulvovaginal candidiasis (VVC; n = 3) was not. Five episodes of proven invasive candidiasis were documented in 4 patients; 1 of these episodes was community acquired in the absence of any other comorbid condition. The first episode of candidiasis occurred earlier in life (median age±standard deviation, 1.5 ± 7.87 years) than infections with environmental mycobacteria (4.29 ± 11.9 years), Mycobacterium tuberculosis (4 ± 3.12 years), or Salmonella species (4.58 ± 4.17 years) or other rare infections (3 ± 11.67 years). Candidiasis was the first documented infection in 19 of the 35 patients, despite the vaccination of 10 of these 19 patients with live bacille Calmette-Guérin. Conclusions: Patients who are deficient in IL-12Rβ1 may have candidiasis, usually mucocutaneous, which is frequently recurrent or persistent. Candidiasis may be the first clinical manifestation in these patients. Keywords: Candida; Interleukin-12 receptor β1 chain; Mycobacterium; Salmonella; primary immunodeficiency.